Cobalt associated with potassium phosphite improves the post-harvest quality of mango cv. Palmer - Jesus, Mariana Oliveira de; Mizobutsi, Gisele Polete; Prates, Paola Junayra Lima; Pinheiro, Juceliandy Mendes da Silva; Oliveira, Moacir Brito de; Mizobutsi , Edson Hiydu (Comunicata Scientiae, 2024)
Mango is a highly perishable climacteric fruit with a short post-harvest period. Therefore, to extend shelf life, the mangoes were treated pre-harvest with a potassium phosphite solution (1.4 g/mL KH2PO4) and a control solution (0 g/mL KH₂PO) associated with different doses of cobalt (0; 48; 64; 80; 112 ml.plant-1) at a density of 1.30 g/mL. The work measured physical, chemical, and biochemical variables. Cobalt and potassium phosphite favored maintaining color and firmness and reduced the respiratory rate. The treatments significantly affected the chemical variables, reduced the soluble solids content, conserved ascorbic acid, and preserved the pH. Foliar application of cobalt and potassium phosphite at pre-harvest is an efficient technique for improving shelf life and maintaining mango quality during storage at room temperature.